Pesan Pendidikan Dari Hadits Permulaan Adzaan Dalam 2002 Mutiara Hadiets Karya M. Hasbi Ash-Shiddieqy - Rafli, Muhamad (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
Adhan is an Islamic symbol that not only marks the time of prayer but also conveys educational values essential for shaping Muslim character. This article examines the educational messages of the hadith on the initiation of adhan as interpreted by Indonesian scholar M. Hasbi ash-Shiddieqy in 2002 Mutiara Hadiets. The study applies library research, using Hasbi’s work as the primary source, supported by relevant literature on hadith and Islamic education. Data were analyzed descriptively and qualitatively through comparison, interpretation, and extraction of educational values. Findings reveal that the hadith on the initiation of adhan contains three central educational messages. First, the importance of intellectual intelligence and courage in reasoning, as exemplified by Umar ibn al-Khattab, which emphasizes cultivating sound reasoning and sharp intellect in Islamic education. Second, the significance of consultation (shura) in important matters as a participatory educational method that nurtures collective thinking, respect for differing opinions, and wise decision-making. Third, the method of legal deduction (istinbath) that prioritizes substantive meaning and public interest (maqasid al-shari‘ah), enabling Islamic education to transcend textualism and respond to contemporary challenges. Thus, Hasbi’s interpretation demonstrates that hadiths serve not only as normative texts but also as pedagogical sources that shape critical, dialogical, and adaptive individuals relevant to modern contexts.